2020
DOI: 10.1039/d0nj03742g
|View full text |Cite
|
Sign up to set email alerts
|

Nano-fluorescent probes based on DNA-templated copper nanoclusters for fast sensing of thiocyanate

Abstract: Thiocyanate (SCN-) is a metabolite of cyanide detoxification, which is considered as a biomarker of environmental tobacco smoke exposure. Herein, a simple, fast and label-free fluorescent sensor was developed to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The results shown in Figure 3C demonstrated that the freshly prepared CuNCs exhibited a uniform spherical shape with a diameter of 5 nm, which was consistent with our previous work. 37 CuNCs could be easily oxidized by gaseous or dissolved oxygen, resulting in their low catalytic activity and poor stability. 38 Therefore, it was necessary to investigate the nanostructure stability of CuNCs.…”
Section: Characterization and Stability Of Dna-templated Cuncsmentioning
confidence: 99%
“…The results shown in Figure 3C demonstrated that the freshly prepared CuNCs exhibited a uniform spherical shape with a diameter of 5 nm, which was consistent with our previous work. 37 CuNCs could be easily oxidized by gaseous or dissolved oxygen, resulting in their low catalytic activity and poor stability. 38 Therefore, it was necessary to investigate the nanostructure stability of CuNCs.…”
Section: Characterization and Stability Of Dna-templated Cuncsmentioning
confidence: 99%
“…The invented fluorescence sensor can detect SCN − with high sensitivity of 4.94 mM in the linear range of 10–100 mM. [ 178 ]…”
Section: Functional Nanomaterials In Assaying Biomarkersmentioning
confidence: 99%
“…The invented fluorescence sensor can detect SCN À with high sensitivity of 4.94 mM in the linear range of 10-100 mM. [178] A reliable inverse micelle approach was used to design highly When fluorescein is bound to the surface of AuNPs, its fluorescence is significantly inhibited. The addition of SCN À turned on the fluorescence due to the competing activity of fluorescein and SCN À towards the surface of AuNPs.…”
Section: Inorganic Species As Biomarkersmentioning
confidence: 99%